Health Versus Wealth During the Covid-19 Pandemic: Saving Lives or Saving the Economy?. Issue 3 (15th October 2021) - Lesschaeve, Christophe; Glaurdić, Josip; Mochtak, Michal
Abstract: Efforts to combat the COVID-19 crisis were characterized by a difficult trade-off: the stringency of the lockdowns decreased the spread of the virus, but amplified the damage to the economy. In this study, we analyze public attitude toward this trade-off using a survey-embedded experiment conducted with a quota sample of more than 7, 000 respondents from Southeast Europe, collected in April and May 2020. The results show that public opinion generally favored saving lives even at a steep economic cost. However, the willingness to trade lives for the economy was greater when the heterogeneous health and economic consequences of lockdown policies for the young and the elderly were emphasized. Free-market views also make people more accepting of higher casualties, as do fears that the instituted measures will lead to a permanent expansion of government control over society.